Flow cytometry with plant cells : analysis of genes, chromosomes and genomes - Doležel, Jaroslav; Greilhuber, Johann; Suda, Jan (Wiley-VCH ; John Wiley [distributor], 2007)
Targeted at beginners as well as experienced users, this handy reference explains the benefits and uses of flow cytometery in the study of plants and their genomes. Following a brief introduction that highlights general considerations when analyzing plant cells by flow cytometric methods, the book goes on to discuss examples of application in plant genetics, genomic analysis, cell cycle analysis, marine organism analysis and breeding studies. With its list of general reading and a glossary of terms, this first reference on FCM in plants fills a real gap by providing first-hand practical hints.- Resumé vydavatel